PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK KVISOFT PADA MATERI BAGIAN TUMBUHAN DAN FUNGSINYA DI KELAS IV SDN 004 SAMARINDA ULU - Gresia Kristinawati; Muhlis; Rosita Putri Rahmi; Khusnul Khotimah; Yana Supriyatna (STKIP Subang, 2025)
The development of the Flipbook Kvisoft media aims to enhance the effectiveness of science learning, specifically on the topic of plant parts and their functions, for fourth-grade students at SDN 004 Samarinda Ulu. This media is designed to be interactive, engaging, and support both students’ and teachers’ needs, thereby increasing motivation, understanding, and reducing boredom in the learning process. This study employed a Research and Development (R&D) method using the 4D development model (Define, Design, Development, and Dissemination). The research development procedure also followed the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of the research and discussion on the development of the Flipbook Kvisoft media for science learning on plant parts and their functions in fourth-grade students at SDN 004 Samarinda Ulu were declared